Dilemmas of Monetary Policy in the Aspect of Polish Integration with the European Monetary Union - Rosiek, Janusz (Dylematy polityki pieniężnej w aspekcie integracji Polski z Europejską Unią Walutową, 2009)
The article tries to present a problem connected with the limitations of the effectiveness led by the monetary policy of the National Bank of Poland. They result above all from: issues concerning unfavourable shaping of chosen aspects of independence of the National Bank of Poland in connection with other European central banks; disturbances of the transmission impulses of the monetary policy to the domestic economic system; loss of sovereignty by the National Bank of Poland after the accession to the European Monetary Union. The presented problems have especially crucial meaning from the point of view of possibilities of interaction by the council of monetary policy on the macroeconomic stabilization in the next years, and also in the context of the future of Poland's membership in the euro zone.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 117-130
Keywords: monetary policy; European Monetary Union; European integration; inflation purpose